Development of a realistic mathematics education (rme)–based learning module on social arithmetic to enhance students' mathematical literacy - Malinda, Ari; Suanto, Elfis; Maimunah (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
This study addresses the low level of students' mathematical literacy, which is partly attributed to the limited availability of teaching materials that explicitly support the development of mathematical literacy skills. The study aimed to develop a learning module based on Realistic Mathematics Education (RME) on the topic of social arithmetic that is valid, practical, and effective in improving students' mathematical literacy skills. The study employed a research and development approach using the 4-D model, consisting of the define, design, develop, and disseminate stages. The participants were seventh-grade students of SMP Negeri 2 Binjai. The results indicate that the developed module achieved a validity level of 93.48% (very valid) based on expert review and one-to-one evaluation, a practicality level of 86.01% (very practical) in the small-group trial and 86.96% (very practical) in the field test, and demonstrated effectiveness as reflected in the significant difference in posttest mean scores between the experimental and control classes. Furthermore, the improvement in students' mathematical literacy skills, measured using the N-gain index, showed a high category in the experimental class (0.7012) and a medium category in the control class (0.4029). These findings indicate that the RME-based learning module is suitable for use as instructional material to enhance students' mathematical literacy skills, as it fulfills the criteria of validity, practicality, and effectiveness.